Polyclonal CD5+/CD19+ B1a lymphocytes after allogeneic stem cell transplantation: a potential diagnostic pitfall - Amir Qorbani; Guofeng Gao; Denis M. Dwyre (Autopsy and Case Reports, 2021)
In adults, B-lymphocytes comprise approximately 10% of circulating lymphocytes. The majority of peripheral B cells are B2 cells (“Mature” B-cells), which function as part of the humoral adaptive immune system. B1 cells (“Innate-like” B cells) are another sub-class of B lymphocytes, considered as innate immune cells with a characteristic phenotype (CD20+, CD27+, CD43+, CD70-, CD11b+, sIgM++, sIgD+) which can be divided into two subtypes; B1a (CD5+): spontaneously produce broadly reactive natural IgM, and B1b (CD5-): can generate T-cell independent, long-lasting IgM. There is very limited data available, indicating a correlation between allogeneic bone marrow transplantation and an increase in B1a cells. Here we present a case of a 17-year-old female with homozygous sickle cell disease (HbSS disease) who underwent hematopoietic stem cell transplant (HSCT). Approximately seven months post-transplant, she was found to have 16% immature mononuclear cells on complete blood count (CBC)-differential report. A follow-up peripheral blood flow cytometry showed that these cells were polyclonal CD5+/CD20+ B-cells, and comprised 66% of lymphocytes. Further workup and follow up failed to reveal any lymphoproliferative disorders. It is important not to misdiagnose these cells as an atypical CD5+ lymphoproliferative disorder. The presence of B1a cells has not been widely reported in non‑neoplastic post-stem cell transplanted patients. This case also adds to and expands our knowledge regarding the presence of increased circulating B1a cells after stem cell transplant in a patient with no history of hematological malignancy.